(untitled) (Scripta : English Department Journal, 2026)
The aims of this research are investigation of teachers’ beliefs, Classroom practices in using literary text, and the factors influenced teacher’s beliefs and practices. This research used descriptive qualitative design. The researcher also used semi-structured interview, Classroom observation, and document analysis as the instrument. The data of the research was the result of the instruments that used in this research. In the results of this research, the researcher found some beliefs based on those categories such as literary text as a valuable tool for language enrichment, selecting appropriate literary text and method based on students’ needs, interest and relevant, students as the actor in learning activity, students’ background knowledge is necessary, teacher must be creative in creating and conducting lesson plan. In incorporating literary text in the Classroom, teacher implemented her beliefs in teaching such as selective use of short story in literary genres, language focused pedagogical strategies, students actively engaged in Classroom activity. However, behind those beliefs and practices, there are some challenges that teacher faced that make it as the factors influenced teacher’s beliefs and practices in teaching. These findings emphasize teacher’s belief and practices and what influenced those beliefs and practices in teaching.